Loss of Myostatin Alters Gut Microbiota and Carbohydrate Metabolism to Influence the Gut–Muscle Axis in Cattle - Chao Hai; Hongyu Gong; Yanan Xu; Xuefei Liu; Chunling Bai; Guanghua Su; Lei Yang; Guangpeng Li (Veterinary Sciences, 2025)
The gut–muscle axis plays a vital role in host metabolism and health. Although the MSTN gene is a well-known negative regulator of muscle growth, its role in intestinal function and metabolism remains unclear. Understanding this connection is crucial for revealing the systemic impact of MSTN gene editing and its potential to improve metabolic efficiency in livestock. In this study, we investigated the influence of MSTN deletion on gut microbiota composition and carbohydrate metabolism in the cecum and colon of cattle. Using integrated metagenomic, metabolomic, serum biochemical, and muscle transcriptomic analyses, we found significant alterations in microbial communities and key metabolic pathways. Hallella and Escherichia in the colon, as well as Alishewanella in the cecum, were closely linked to carbohydrate metabolism. Differential microbes and metabolites influenced key metabolic pathways, including glycolysis/gluconeogenesis and lipopolysaccharide biosynthesis. Functional gene analysis identified Bacteroides as the most critical bacterium affecting glycolysis/gluconeogenesis. Additionally, genes related to carbohydrate esterases were upregulated. These changes correlated with reduced serum glucose and insulin levels while increasing muscle gene expression related to glucose-to-lactose conversion. Overall, MSTN gene editing alters gut microbiota composition and carbohydrate metabolism in the cecum and colon, thereby influencing host glucose metabolism and energy homeostasis.